Clinical, Laboratory, and Short-Term Outcomes in Neonatal Nonketotic Hyperglycinemia - Celik, Muhittin; Akdeniz, Osman (Kowsar Corp, 2021)
Background: Nonketotic hyperglycinemia (NKH) is a rare metabolism disorder with autosomal recessive transmission. Newborn infants characteristically present with hypotonia, lethargy, convulsions, and apnea and are generally lost within the first year of life. Objectives: The aim of this study was to evaluate the clinical characteristics, laboratory findings, and short-term results of infants diagnosed with NKH. Methods: The retrospective study included 10 infants diagnosed with NKH between August 2013 and July 2020. The clinical characteristics, laboratory findings, treatment methods, and short-term outcomes of the patients were evaluated. Results: The age range of patients (50% males vs. 50% females) was 2 -8 days on presentation. The complaints on presentation were decreased breastfeeding, lethargy, convulsions, hiccups, apnea, and respiratory problems. In the physical examination, significant hypotonia and reduced or absence of newborn reflexes were predominant. Mechanical ventilation (MV) was required for nine patients. The cerebral spinal fluid/serum glycine ratio was > 0.08 in all patients, with median value of 0.19 (range: 0.12 -0.30). The presence of a burst suppression pattern on electroencephalography and an increase in the glycine peak in magnetic resonance spectroscopy were the supportive diagnostic findings. Mutation analysis was performed on one patient. Seizures resistant to treatment were controlled with levetiracetam in three patients and dextromethorphan in one patient. Conclusions: According to the results, the most common clinical findings in NKH were severe hypotonia, seizure, and encephalopathy. In some cases, with resistant seizures, levetiracetam was found to be effective.
Keywords: Nonketotic Hyperglycinemia; Hypotonia; Levetiracetam; Newborn